Touching Spirit Bear - Mikaelsen, Ben, 1952- (New York : HarperCollins Publishers, 2001)
After his anger erupts into violence, Cole, in order to avoid going to prison, agrees to participate in a sentencing alternative based on the native American Circle Justice, and he is sent to a remote Alaskan Island where an encounter with a huge Spirit Bear changes his life.
Keywords: Juvenile delinquents -- Rehabilitation -- Fiction; Anger -- Fiction; Forgiveness -- Fiction; Child abuse -- Fiction; Tlingit Indians -- Fiction; Indians of North America -- Alaska -- Fiction